Exchange rate pass-through to inflation in Egypt: A structural VAR approach - Omneia Helmy; Mona Fayed; Kholoud Hussien (Review of Economics and Political Science (REPS), 2018)
Purpose - The theoretical and empirical literature stipulated that exchange rate shocks do influence the domestic price of imports. Hence, this paper aims to investigate the underlying relationship between the exchange rate and prices known as the exchange rate pass-through. Design/methodology/approach - The paper uses a structural vector auto-regression (SVAR) model, drawing on Bernanke (1986) and Sims (1986), to empirically examine and analyze the pass-through of exchange rate fluctuations to domestic prices in Egypt. Findings - The empirical results of the monthly data between 2003 and 2015 revealed that the exchange rate pass-through in Egypt is fairly substantial but incomplete and slow in the three price indices [IMP, producer price index and consumer price index (CPI)]. However, the impact is more prominent for consumer prices than for any other price index. This finding could be attributed to the fact that the CPI in Egypt is composed of a relatively large number of subsidized commodities and goods with administered prices as well as the authorities' behavior in manipulating prices (i.e. export ban). This is expected to weaken the transmission of exchange rate shocks. Practical implications - The result has interesting implications for Egypt's ability to attain an effective inflation targeting regime. Originality/value - The study contributes to the literature by assessing the effect of changes in the exchange rate (the Egyptian vis-à-vis the US) on prices using an updated time series from 2003 to 2015. It addresses the limitations of the study of Nafie et al. (2004), which found no strong relationship between the exchange rate and inflation rate in the Egyptian context. One of these limitations was using the CPI, as the only price index.
Keywords: 330; Monetary policy; Inflation rate; Exchange rate pass-through; Structural vector auto-regression